Advancing voltage regulation techniques in electrical distribution grids - Batalin, Viktor (National Technical University "Kharkiv Polytechnic Institute", 2024)
The relevance and importance of the development and implementation of innovative methods for improving the process of voltage regulation in electrical distribution grids is determined. The shortcomings of the traditional methods used to regulate voltages in electrical distribution grids have been identified and ways of their improvement have been proposed, the use of which will improve the efficiency of the functioning of electrical grids.
Keywords: electrical grids; voltage; regulation methods; distributed generation; renewable energy sources; energy storage; parameter optimization